Potential for Nordic-Baltic security cooperation: Shared threat perception strengthens regional collaboration - Christian Opitz (Stiftung Wissenschaft und Politik (SWP), 2015)
All the Nordic and Baltic states are concerned about the deteriorating security situation in northern Europe. Most of all, military tensions in the Baltic region engender a collective threat perception vis-à-vis Russia. The pressure to respond is boosting a historically rooted security cooperation between the Nordic and Baltic states. A shifting of priorities is becoming apparent within the institutional cooperation, which is moving from a forum of exchange towards a shared framework of action. The countries involved are responding to traditional military threats and new security challenges with intensified and innovative cooperation. This problem-driven Nordic-Baltic security cooperation could also serve as a model for other regional formats, such as the Visegrád Group. (SWP Comments)
Keywords: 320